Analyzing Translation Errors in Indonesian-English Business Letters - Aldha Williyan; Umar - Umar; Vica Via Vanesa; Ai Nurul Aini (STIBA IEC JAKARTA, 2023)
This paper discussed the translation error from a business letter made based on American Translation Association (ATA's) made by EFL Learners'. In this research, the researchers used a descriptive qualitative method. The data source in this research is two EFL Learners' who are in translation class with better English skills than other data. Data collection in this study was carried out by taking two data from a total of 36 business letter translating task data given by translation class lecturers. The data is classified based on the type of error according to ATA's Framework for Standard Error Making Classification. The results of the analysis show that there are 18 translation errors in 11 types of 26 types of translation errors with style error as the most frequently found error. Style error is the error that has the highest nominal by appearing five times out of 18 the number of errors with a percentage 27,8%. Finding errors from the two data proves that EFL Learners' who are studying translation studies still have deficiencies. Educators and students must work together so that translation errors produced by EFL Learners' can be reduced.